Innovation, research and development management - Gilbert, Patrick; Bobadilla, Natalia; Gastaldi, Lise; Le Boulaire, Martine; Lelebina, Olga (London, UK : ISTE, Ltd. ; Hoboken, NJ : John Wiley & Sons, Inc., 2018)
In today's business environment, as organizations constantly seek to growth and develop through the optimization of their innovative and creative potential, understanding the critical issues and management practices in R & D is essential. This book provides a critical revaluation of the state of the art issues and concepts in R & D management. The views expressed are those of leading French researchers and professionals in this field, fed by empirical studies in national and international firms.
3.2. Creativity: between individual attribute and social process3.2.1. Individual creativity; 3.2.2. Creativity as an idea production process; 3.2.3. Creativity as a social process; 3.3. Ingredients and negative effects of slack reductions on creativity; 3.3.1. Slack reduction components; 3.3.2. Human slack reduction effects; 3.3.3. "Financial slack" reduction effects; 3.3.4. Temporal slack reduction effects; 3.3.5. Spatial slack reduction effects; 3.4. Mechanisms linking slack reduction and creativity; 3.4.1. Focus of attention; 3.4.2. Ability to "travel through time."
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed September 05, 2018).
John Wiley and Sons
Keywords: Research, Industrial -- Management; Technological innovations -- Management; Recherche industrielle -- Gestion; Innovations -- Gestion; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Research, Industrial -- Management; Technological innovations -- Management